Tinjauan Hukum Islam Terhadap Implementasi Akad Mudharabah Di Perbankan Syariah Modern - Dwi Anisa Delia; Mohd Winario; Diany Mairiza (EL-EMIR Institute, 2025)
The implementation of the Musyarakah contract in business capital financing within Islamic banking in Indonesia plays a crucial role in supporting economic growth based on sharia principles. Through a qualitative approach and case studies on several leading Islamic banks, the research shows that Musyarakah is an effective profit-sharing financing instrument, capable of increasing business capital while strengthening the partnership between banks and customers. However, there are several challenges that need to be addressed, such as the complex management of business risks, the need for transparency in profit distribution, and ensuring that financing practices comply strictly with sharia regulations. To optimize the implementation of the Musyarakah contract, Islamic banks need to enhance their risk management capabilities and provide more intensive education to customers so they better understand the profit-sharing mechanism. Additionally, consistency in applying sharia principles is a crucial factor to ensure the sustainability and trustworthiness of Musyarakah-based financing. These findings contribute significantly to the development of more effective and sustainable sharia financing in Indonesia’s banking sector.